2023
DOI: 10.1063/5.0168293
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the potential of hexaferrite–spinel ferrite composites: Microstructure-induced colossal permittivity and relaxation phenomena

Hodam Karnajit Singh,
Prajna P. Mohapatra,
Subingya Pandey
et al.

Abstract: The solid-state synthesized dense ceramic composite, consisting of M-type hexaferrite Ba0.5Sr0.5Fe12O19 and inverse spinel ferrite Ni0.3Co0.2Zn0.5Fe2O4 (NCZFO) with varying concentrations, demonstrates the presence of apparent colossal permittivity along with dielectric relaxation behaviors at the higher frequency regions for all the composites. This phenomenon manifests as a giant dielectric permittivity of approximately 105 at 1 kHz, gradually decreasing to around 103 at 1 MHz at room temperature. It can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…It has been observed that the bulk properties of many conducting materials are best represented by the addition of a constant phase element (Q) in parallel with R and C [56]. The presence of Q can be attributed to the deviation of the impedance response from the ideal Debye relaxation behavior [57]. Q = A 0 (jω) n , where A 0 and n are temperature dependent parameters.…”
Section: Impedance Spectroscopymentioning
confidence: 99%
“…It has been observed that the bulk properties of many conducting materials are best represented by the addition of a constant phase element (Q) in parallel with R and C [56]. The presence of Q can be attributed to the deviation of the impedance response from the ideal Debye relaxation behavior [57]. Q = A 0 (jω) n , where A 0 and n are temperature dependent parameters.…”
Section: Impedance Spectroscopymentioning
confidence: 99%